Entrepreneurial Education Strategy at Islamic Boarding School in Empowering Students with Entrepreneurship Skills - Badawi, Akhmad (Budapest International Research and Critics University, 2021)
Life is very competitive, and the difficulties of getting work in the formal and industrial sectors in this globalized era is a very difficult life obstacle that we have to face. The imbalance of the workforce that continues to increase every year with employment or industrial growth is a very serious problem in Indonesia. Facing this phenomenon, of course, it is necessary to prepare a generation that is reliable, competitive, and independent and has an entrepreneurial spirit. This effort can be realized through educational institutions, namely by implementing entrepreneurship education. Islamic boarding school with its character and independence is an educational institution that is quite ideal for implementing character education in it. The purpose of this paper is to explain the strategy of Entrepreneurship Education at Islamic Boarding Schools in Empowering Student with entrepreneurial skills. The method used to obtain data in writing this journal is an exploratory literature study. Data obtained from internet media, and relevant books. The results of this article can explain the nature, conditions, problems and obstacles, strategies and benefits of implementing entrepreneurship education in Islamic boarding schools.